Income-dependent equivalence scales: A fresh look at German micro-data - Jan Marvin Garbuszus; Notburga Ott; Sebastian Pehle; Martin Werding (The Journal of Economic Inequality, 2021)
Income inequality and poverty risks receive a lot of attention in public debates and current research. To make income comparable across different types of households, applying the "(modified) OECD scale" – an equivalence scale with fixed weights for each household type – has become a quasi-standard in research. Instead, we derive a base-dependent equivalence scale allowing for scale weights that vary with income, building on micro-data from Germany. Our results suggest that appropriate equivalence scales are much steeper at the lower end of the income distribution than they are for higher income levels. We illustrate our findings by applying them to data on family income differentiated by household types. It turns out that using income-dependent equivalence scales matters for applied research on income inequality, especially if one is concerned with the composition, not just the size of the population at poverty risk.
Keywords: 300; Equivalence scales; Household income; Household needs; Inequality measurement; Poverty risks